2023
DOI: 10.1007/s11104-023-06068-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing root biomass derived carbon input to agricultural soils by genotype selection – a review

Abstract: Background and aims Soil carbon sequestration can play an important role in mitigating climate change. Higher organic C inputs to agricultural soils are needed in order to increase soil organic carbon (SOC) stocks. Genotype selection and breeding towards increased root biomass may enhance root C inputs to the soil and could therefore be a promising, easy-to-implement management option for potentially increasing C sequestration. However, an increase in root C inputs may compromise yield, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The mutant lines with high root biomass recorded grain yields above average under drought stress conditions ( Table 4 ). The current study found a strong correlation between root biomass and grain yield under drought stress conditions ( Figure 1 ), suggesting optimal root biomass allocation could increase soil carbon sequestration, increasing yield and mitigating climate change effects ( Heinemann et al., 2023 ; Shamuyarira et al., 2023 ).…”
Section: Discussionmentioning
confidence: 58%
“…The mutant lines with high root biomass recorded grain yields above average under drought stress conditions ( Table 4 ). The current study found a strong correlation between root biomass and grain yield under drought stress conditions ( Figure 1 ), suggesting optimal root biomass allocation could increase soil carbon sequestration, increasing yield and mitigating climate change effects ( Heinemann et al., 2023 ; Shamuyarira et al., 2023 ).…”
Section: Discussionmentioning
confidence: 58%
“…Roots represent the least certain part of the description of the C cycle in the soil and in ecosystems, because C is lost during growth to the soil in the form of exudates and mechanically abraded surface tissues and due to the decay of some roots during growth [ 52 ]. According to a review of previous studies, the net C deposited in the roots of grasses and dicotyledonous crops represents 16 and 10% of total assimilated C, respectively, and it is an important aspect of soil C sequestration [ 54 ]. Clivot et al [ 43 ] calculated plant C extra-root material (C from root turnover and root exudates) as 65% of root C [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This biomass includes all parts of the plant, such as roots, stems, leaves, and fruits. It is a crucial component of ecosystems as it serves as a source of energy and nutrients for various organisms [50][51][52][53][54]. Ciplukan seeds originating from the low and medium plains showed biomass that was not significantly different.…”
Section: Plant Biomassmentioning
confidence: 99%